Association between socioeconomic status, dental caries status and body mass index of children from two preschools in Kuantan: A preliminary report - Ramli, Muhammad Zaki; Nina Suhaity, Azmi; Ismail, Ahmad Faisal (International Association for Dental Research - Malaysia Section (IADR-MalSec), 2021)
The association between dental caries and body mass index (BMI) in children has been researched extensively. The socioeconomics status of the families is said to play a significant role in determining the BMI and caries status of the preschool children. Preschool children’s dental caries and BMI statuses are of concern among parents. However, the findings in previous research that relate socioeconomic status with dental caries and BMI have been shown to have contradictory results. Thus, this study was conducted with the aim to examine the association between socioeconomic, dental caries and BMI statuses among preschool children in two preschools in Kuantan. The socioeconomic data of the childre’s families were obtained using a questionnaire. He dental caries was evaluated by a paediatric dentist according to the decayed, missing, and filled teeth (dmft) index. Statistical analyses were performed using SPSS v.22.0 program. A total of 55 Malay preschool children were sampled. The study found no significant association between BMI type and dmft, and no significant association between BMI and household income in chi-square test at p < .05. However, a significant difference was found between dmft and socioeconomic status (Kruskal-Wallis test, H statistic = 81.7568 (1, N = 110), p-value < .00001). Further studies with a higher number of subjects are required to increase the reliability of the findings of this preliminary report.